Relating knowledge, attitude and practice of antibiotic use to extended-spectrum beta-lactamase-producing Enterobacteriaceae carriage: results of a cross-sectional community survey. Issue 3 (5th March 2019) - Mo, Yin; Seah, Ivan; Lye, Pei Shi Priscillia; Kee, Xiang Lee Jamie; Wong, Kien Yee Michael; Ko, Kwan Ki Karrie; Ong, Rick Twee-Hee; Tambyah, Paul A; Cook, Alex R
Abstract : Objectives: To study the correlation between knowledge, attitude and practices (KAP) of antibiotic consumption with epidemiology and molecular characteristics of extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE) carriage, in order to identify modifiable factors and public health interventions to reduce prevalence of multidrug-resistant organism colonisation in the community. Design: Cross-sectional questionnaire of KAP towards antibiotic use and collection of stool samples or rectal swabs. ESBL-PE isolates obtained underwent whole genome sequencing to identify resistance genes. Setting: A densely populated community in Singapore. Participants: There were 693 healthy community-dwelling questionnaire respondents. Out of which, 305 provided stool samples or rectal swabs. Results: The overall knowledge of antibiotic use was poor (mean score 4.6/10, IQR 3.0–6.0). 80 participants (80/305, 26.2%) carried at least one ESBL-PE isolate. The most common ESBL-PE was Escherichia coli sequence type 131 carrying CTX-M type beta-lactamases (11/71, 15.5%). Living overseas for >1 year (OR 3.3, 95% CI 1.6 to 6.9) but not short-term travel, recent hospitalisation or antibiotic intake was associated with ESBL-PE carriage. Interestingly, higher knowledge scores (OR 2.0, 95% CI 1.03 to 3.9) and having no leftover antibiotics (OR 2.4, 95% CI 1.2 to 4.9) were independent factors associated with ESBL-PE carriage in the multivariate logistic regression model. Conclusions: While the role of trans-border transmission of antimicrobial resistance is well known, we may have to examine the current recommendation that all antibiotics courses have to be completed. Clinical trials to determine the optimum duration of treatment for common infections are critically important.